Correlations between melioidosis seroprevalence in livestock and meteorological factors in Peninsular Malaysia - Musa, Hassan Ismail; Hassan, Latiffah; Panchadcharam, Chandrawathani; Zakaria, Zunita; Abdul Aziz, Saleha (ResearchersLinks, 2024)
Melioidosis is an emerging saprozoonosis which constitutes animal and public health problems in the endemic areas. This study examined the effects of meteorological factors on distribution, trends and patterns of melioidosis seroprevalence in livestock in Peninsular Malaysia. Data on melioidosis surveillance and climatic factors were obtained from the Department of Veterinary Services (DVS) and Malaysian Meteorological Department (MMD). Seroprevalence of the disease in different animal species were calculated and the relationships between the prevalence and climatic factors were examined. A total of 72,941 animals were sampled from 1,765 livestock farms across all the states and tested, out of which 4,516 (6.20%, 95% CI 6.02-6.37) were serologically positive for melioidosis. Correlation analysis of seroprevalence and the climatic factors showed strong, positive and statistically significant correlation (r =0.58, 95% CI, 0.12-0.87, p=0.047) between the disease prevalence and average monthly rainfall. There was a moderate but non-significant positive correlation (r =0.47, 95% CI, 0.13-0.82, p=0.11) between disease prevalence and average monthly rainy days and weak and non-significant correlation (r =-0.23, 95% CI, 0.71-0.39, p=0.47) with the average monthly wind speed. Animal melioidosis is widespread within Peninsular Malaysia where the disease appears to occur more in the domestic compared to wild animals. The study showed that more resources and attention appeared to have been placed on small ruminants compared to other livestock species. Amount of rainfall recorded during the previous decade may have contributed to the occurrence of the disease in livestock over the years.